Titanium dioxide/zeolite integrated photocatalytic adsorbents for the degradation of amoxicillin - Kanakaraju, D.; Kockler, J.; Motti, C.A.; Glass, B.D.; Oelgemöller, M. (Elsevier, 2015)
Integrated photocatalytic adsorbents (IPA) prepared from TiO2 and natural zeolite were applied to amoxicillin (AMX) degradation. The acid-alkali pre-treated zeolite annealed at 300°C under nitrogen resulted in the best degradation of AMX. The superior performance of this IPA material was explained using scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS) and X-ray diffraction (XRD). SEM analysis showed an uneven surface as a result of TiO2 cluster deposition, which provides more active sites for adsorption and degradation. XRD results revealed that peaks from more photoactive anatase were more prominent in this IPA material. EDS analyses also confirmed the presence of high amounts of TiO2. Despite their large TiO2 loadings, comparison experiments with untreated zeolite suggested that the pores are still available for adsorption. The overall performance of the IPA material for the degradation of AMX was thus attributed to the adsorption capability of the zeolite carrier, the photocatalytic activity of TiO2 coating and acid-catalyzed hydrolysis ('capture & destroy'). Degradation products resulting from TiO2/zeolite IPA-induced hydrolysis were identified by liquid chromatography-mass spectrometry (LC-MS) prior to photocatalytic treatment. AMX and its thermal degradants were almost completely removed after 240min of irradiation. The efficiency of the developed TiO2/zeolite material provides a potentially economical way of degrading pharmaceutical compounds and recovering photocatalysts simultaneously.